Differential incidence and type of spasm according to coronary arterial location. Issue 4 (June 2016) - Sueda, Shozo; Kohno, Hiroaki
Abstract : Background: We encounter a less provoked spasm in the left circumflex artery (LCX) by acetylcholine (ACh) testing compared with left anterior descending artery and right coronary artery (RCA) in the real world. Objectives: We investigated the clinical characteristics of provoked spasm in the LCX by ACh testing. Methods: We retrospectively analyzed consecutive 1392 ACh testing over 20 years (1991–2011). The maximal ACh dose was 100 μg into the left coronary artery and 80 μg into the RCA. Positive spasm was defined as transient of more than or equal to 90% narrowing and usual chest symptoms or ischemic ECG changes. Results: Positive provoked spasm was recognized in 622 patients (44.7%) including 456 RCA spasms, 448 left anterior descending artery spasms, and 176 LCX spasms. LCX-provoked spasm was significantly lower than other vessels ( P <0.001). LCX-provoked spasm was observed in 176 patients, of whom 113 patients (64.2%) had triple-vessel spasm, 46 patients (26.1%) had double-vessel spasm, and 17 patients (9.7%) had single-vessel spasm. More than 90% patients with LCX-provoked spasm had multiple spasms. Of 17 patients with LCX single-vessel spasm, 15 patients (88.2%) had focal spasm. Conclusion: Under a maximal ACh dose of 100 μg into the left coronary artery, LCX-provoked spasm was significantly lower than other vessels and more than 90% of patients had multiple spasms.